PERJANJIAN YANG DIBUAT MENGAKIBATKAN PERSELISIHAN - Tamaulina Br.Sembiring; Jeni Alfikri Ginting; Riza Alif Pasha; Vieri Rivaldo Hasibuan (Jurnal Cakrawala Ilmiah, 2026)
Agreements are one of the legal instruments used to regulate relationships between parties in a lawful and legally binding manner. However, it is not uncommon for agreements to actually cause disputes due to unclear clauses, violations of rights, or errors in execution. This journal discusses the factors that cause disputes in agreements, the dispute resolution mechanisms, as well as preventive measures to ensure agreements can be implemented effectively and what efforts can be made to prevent conflicts arising from agreements. The research method used is descriptive qualitative with a library research approach. The results of the study show that careless drafting of agreements, poor communication, and non-compliance with the law are the main factors causing disputes